Unexpected Levels of Biological Activity during the Polar Night Offer New Perspectives on a Warming Arctic - Berge, Jørgen; Daase, Malin; Renaud, Paul E; Ambrose, William G; Darnis, Gerald; Last, Kim S; Leu, Eva; Cohen, Jonathan H; Johnsen, Geir; Moline, Mark A; Cottier, Finlo (Current Biology, 2015)
The current understanding of Arctic ecosystems is deeply rooted in the classical view of a bottom-up controlled system with strong physical forcing and seasonality in primary-production regimes. Consequently, the Arctic polar night is commonly disregarded as a time of year when biological activities are reduced to a minimum due to a reduced food supply. Here, based upon a multidisciplinary ecosystem-scale study from the polar night at 79ºN, we present an entirely different view. Instead of an ecosystem that has entered a resting state, we document a system with high activity levels and biological interactions across most trophic levels. In some habitats, biological diversity and presence of juvenile stages were elevated in winter months compared to the more productive and sunlit periods. Ultimately, our results suggest a different perspective regarding ecosystem function that will be of importance for future environmental management and decision making, especially at a time when Arctic regions are experiencing accelerated environmental change.